NATIONAL-HISTORICAL FOUNDATIONS OF FORMATION OF AN ACTIVE POSITION IN YOUNG PEOPLE (Scientific journal of the Fergana State University, 2024)
The article examines the essence and social significance of concepts such as "national-historical foundations of active position", "active position", "position", "vital position", "social position". The national-historical role of the active social position of young people in the process of establishing a civil society, building a legal democratic state and modernization in the conditions of the new Uzbekistan is revealed. The active social position is analyzed as an important factor in the formation of the consciousness of modern youth, and the importance of young people's desire for innovation and intellectual potential is considered.